2003
DOI: 10.1002/sia.1533
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of PVC endotracheal tubes by oxygen glow discharge to reduce bacterial adhesion

Abstract: A d.c. oxygen glow discharge was used to modify medical-grade poly(vinyl chloride) (PVC) to study how surface chemistry and hydrophilicity influence Pseudomonas aeruginosa adhesion. The effects of plasma exposure time on the resulting surface, including chemical composition, wettability and roughness, were assessed using x-ray photoelectron spectroscopy, contact angle measurements and atomic force microscopy analysis. A significant alteration in the hydrophilicity of the native PVC surface was observed after o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 26 publications
5
84
0
Order By: Relevance
“…24,29 The change is further supported by the increased hydrophilicity of the nano-R materials, as seen in previous studies. 30,31 However, the O/C ratio for these materials did not change significantly with the 0.1% lipase treatment suggesting that bacterial adhesion and growth on the surface of the nano-R material is influenced by other factors than surface chemistry.…”
Section: Discussionmentioning
confidence: 97%
“…24,29 The change is further supported by the increased hydrophilicity of the nano-R materials, as seen in previous studies. 30,31 However, the O/C ratio for these materials did not change significantly with the 0.1% lipase treatment suggesting that bacterial adhesion and growth on the surface of the nano-R material is influenced by other factors than surface chemistry.…”
Section: Discussionmentioning
confidence: 97%
“…21,23,26 Boks et al reported that bond strengthening for four strains of S. epidermidis on a hydrophobic surface was fast and limited to a minor increase, while strengthening of the bonds on a hydrophilic surface increases significantly with contact time. 33 As water molecules adjacent to a hydrophobic surface are not able to form hydrogen bonds with that surface (hydrophobic effect), bacterial adhesion to a hydrophobic specimen is brought about by an entropically favorable release of water molecules.…”
Section: Discussionmentioning
confidence: 99%
“…19 Recently, there have been a number of reports on the impact on bacterial adhesion of surface roughness, wettability, and other physical properties of the actual solid materials themselves. [20][21][22][23][24][25][26][27][28] However, most of this research has been on dental implants, on the basis of conditions found in the mouth. [25][26][27][28] There is little research into the adhesion of S. epidermidis to other medical materials used in clinical practice, and their results were mostly inconsistent.…”
mentioning
confidence: 99%
“…Based on the data, the C12p atomic content is significantly lower than expected for a standard PVC containing no additives originating from the presence of several additives and also X-ray degradation [48]. Due to the same reason, a considerable amount of Ols is detected on the sample 1 surface which is not a typical element found in standard PVC.…”
Section: Surface Chemistry Analysismentioning
confidence: 77%